2015
DOI: 10.1186/s12967-015-0611-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor pathway mutation and expression profiles in cervical squamous cell carcinoma: therapeutic implications

Abstract: BackgroundCervical squamous cell carcinoma (CSCC) is a major cause of female mortality worldwide. This study has examined epidermal growth factor receptor (EGFR) pathway markers that represent actionable pharmacological targets.MethodsHPV16 positive CSCCs (n = 105 patients) from Madhya Pradesh, India were screened for KRAS and PIK3CA mutations by PNA-clamp real-time PCR. Immunohistochemistry (IHC) was performed for EGFR, PIK3CA, PTEN, phospho-AKT, phospho-mTOR and phospho-44/42 MAPK (ERK1/2).ResultsKRAS mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
2
19
1
Order By: Relevance
“…Our results are close to that of Bumrungthai et al [13] and Kersemaeker et al [19] who observed worse prognosis associated with EGFR overexpression. The results are also similar to that of Adimi et al [12] and Tian et al [17] who stated that high EGFR expression has shown to be involved in poor response to radiotherapy; and significantly related to poor DFS in patients treated with chemo radiation or surgery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are close to that of Bumrungthai et al [13] and Kersemaeker et al [19] who observed worse prognosis associated with EGFR overexpression. The results are also similar to that of Adimi et al [12] and Tian et al [17] who stated that high EGFR expression has shown to be involved in poor response to radiotherapy; and significantly related to poor DFS in patients treated with chemo radiation or surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Noordhuis et al [18] agreed with us; they found a significant correlation between EGFR and ERK staining. This simple linear correlation wasn't detected by Bumrungthai et al [13]. This contradiction may be due to changes in immunohistochemical protocols.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our data therefore also suggest a correlation between TP53 mutations and type II carcinoma, but note that this is based on only 3 tumours. No correlation between TP53 and DFS or OS could be demonstrated based on our findings [37, 38]. …”
Section: Discussioncontrasting
confidence: 54%
“…However,our results showed no significant toEGFR expression and intensity in endometrial cancer according histological type (P>0.05.Results of [12] found that EGFR expression was lower in type II(34%) compared with type I EC (46%) and reported that EGFR expression positive in 60(46%)cases endometriod out of 130 and 36(36%) cases uterine serous papillary out of 101. [33]explain that EGFR expression was found in 60 (59.4%)cases out of 101 ofsquamous cell carcinoma. Our findings explain clearly, that the development and progression of endometrial cancer did not affected by p53 and EGFR expression; also these results need other confirmations.…”
Section: : Egfr Expression and Intensity In Endometrial Cancer Accmentioning
confidence: 95%